Diagnostic yield of FDG-PET/CT in fever of unknown origin: a systematic review, meta-analysis, and Delphi exercise. Issue 9 (September 2017) - ; Miller, R.; Llewelyn, M.; Jenkins, N.; Lambourne, J.; Cosgrove, C.; Moore, E.; Conlon, C.; NicFhogartaigh, C.; Agranoff, D.; Ustianowski, A.; Parker, B.; et al.
Abstract : Aim: To perform a systematic review, meta-analysis and Delphi exercise to evaluate diagnostic yield of combined 2-[ 18 F]-fluoro-2-deoxy-d -glucose (FDG) positron-emission tomography and computed tomography (FDG-PET/CT) in fever of unknown origin (FUO). Materials and methods: Four databases were searched for studies of FDG-PET/CT in FUO 1/1/2000–1/12/2015. Exclusions were non-English language, case reports, non-standard FDG radiotracer, and significant missing data. Quality was assessed by two authors independently using a standardised tool. Pooled diagnostic yield was calculated using a random-effects model. An iterative electronic and face-to-face Delphi exercise generated interspeciality consensus. Results: Pooled diagnostic yield was 56% (95% confidence interval [CI]: 50–61%, I 2 =61%) from 18 studies and 905 patients. Only five studies reported results of previous imaging, and subgroup analysis estimated diagnostic yield beyond conventional CT at 32% (95% CI: 22–44%; I 2 =66%). Consensus was established that FDG-PET/CT is increasingly available with an emerging role, but there is prevailing variability in practice. Conclusion: There is insufficient evidence to support the value of FDG-PET/CT in investigative algorithms of FUO. A paradigm shift in research is needed, involving prospective studies recruiting at diagnosis of FUO, with updated case definitions and hard outcome measures. Although these studies will be a significant undertaking with multicentre collaboration, their completion is vital for balancing both radiation exposure and costs against the possible benefits of utilising FDG-PET/CT. Highlights: A systematic review identified 18 eligible studies, 905 patients, of FDG-PET/CT in FUO. Pooled diagnostic yield was 56% (95%CI 50–61%), I 2 =61%. Sub-group analysis of diagnostic yield over conventional CT was 32% (95%CI 22–44%) I 2 =66%. Iterative Delphi Surveys generated interspeciality consensus on the topic. There is insufficient evidence to support the value of FDG-PET/CT in investigative algorithms.